Sickness and absence from work among municipal workers: A cross-sectional study in the extreme south of Brazil (Research, Society and Development, 2021)
Objective: To identify work leaves, granted by sick leave, justified by illnesses and injuries of workers from municipal public sector departments, in the extreme south of Brazil. Methodology: This is a cross-sectional descriptive and analytical research, with a quantitative approach. The data collection was extracted from a bank in the Occupational Health Sector in the municipality of the study. In the previous analysis of the data, descriptive statistics was applied. As these are secondary data, the ethical guidelines of the National Health Council were respected. Results: Of the 4,120 labor absenteeism of municipal employees, for sick leave, 52.6% were teachers servers; it was found that, despite absence from work, they were justified by up to 6 diagnoses, coded according to the international classification of diseases, 95.6% were recorded by a diagnosis; of the set of diseases noted in health licenses, 68% fell into 5 groups of the international classification of diseases: “Factors influencing health status and contact with health services”; “Diseases of the Musculoskeletal System and Connective Tissue"; “Respiratory System Diseases ”; “Diseases of the Digestive System”; Symptoms, signs and abnormal clinical and laboratory findings, not elsewhere classified, when the category code from the international classification is taken into account, the framework of the set of diseases covered 367 categories. Conclusion: It is hoped to contribute to the development of management strategies for workers' and work environments' safety and healthy conditions.